Meissen, (Kingdom of Saxony,) Nov'br 20th, 1848. To Fred'k A. Mayo, Esq'r, Richmond, Va.: Dear sir, permit me to address myself to you concerning the Eisenmenger possessions of land in the counties of Grayson, Monroe, Montgomery, Tazewell and Wythe, (Western Virginia,) of which you know more than any one else - Geyer, Karl Andreas, 1809-1853 (Document (Virginia. General Assembly), 1848)
November 20, 1848 Letter from Charles Andrew Geyer of Meissen, Saxony to Frederick A. Mayo in Richmond, requesting information about the western Virginia counties on land originally purchased by Lewis Eisenmenger. Of note, Mayo emigrated from Germany and worked with Geyer in assisting Germans who wished to settle in Virginia.